2018
DOI: 10.3389/fnmol.2018.00240
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phenotypes of Shank2 Mouse Models Reflect Neuropsychiatric Spectrum Disorders of Human Patients With SHANK2 Variants

Abstract: The SHANK scaffolding proteins are important organizers for signaling proteins in the postsynapse of excitatory neurons. The functional significance of SHANK proteins becomes apparent by the wide spectrum of neurodevelopmental and neuropsychiatric disorders associated with SHANK variants in human patients. A similar diversity of neuropsychiatric-like phenotypes is described for numerous Shank2 and Shank3 knockout (KO) mouse lines. In this review, we will focus on and discuss the experimental results obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 109 publications
(161 reference statements)
1
53
0
Order By: Relevance
“…SHANK genes reside on autosomes, and SHANK variants are randomly distributed across male and female subjects. So far, only copy number variant (CNV) deletions encompassing the SHANK1 gene segregated in male carriers with high-functioning autism and showed a clearly reduced penetrance in female individuals (Sato et al, 2012 ) and some SHANK variants have been found in male autistic patients that were inherited from healthy mothers (for a recent review see (Eltokhi et al, 2018 )).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHANK genes reside on autosomes, and SHANK variants are randomly distributed across male and female subjects. So far, only copy number variant (CNV) deletions encompassing the SHANK1 gene segregated in male carriers with high-functioning autism and showed a clearly reduced penetrance in female individuals (Sato et al, 2012 ) and some SHANK variants have been found in male autistic patients that were inherited from healthy mothers (for a recent review see (Eltokhi et al, 2018 )).…”
Section: Discussionmentioning
confidence: 99%
“…SHANK proteins (SHANK1, SHANK2 and SHANK3) are scaffolding proteins at the postsynaptic site of excitatory synapses in the central nervous system (Kreienkamp, 2008 ), crucial for the formation, organization and signaling of excitatory synapses. SHANK gene variants have been associated with ASD, intellectual disability and schizophrenia (Leblond et al, 2014 ; Eltokhi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we focused our experiments on mice lacking the Shank2 protein. To date, three different genetic constructions of the model exist (reviewed in Eltokhi et al, 2018 ): deletion of exon 16 [knock out ( Schmeisser et al, 2012 ; Ey et al, 2013 ; Lim et al, 2016 ), conditional knock out in Purkinje cells ( Peter et al, 2016 )], deletion of exons 15 and 16 [knock out ( Won et al, 2012 ; Lee et al, 2015 ; Lim et al, 2016 ), conditional knock out in Purkinje cells ( Ha et al, 2016 ), conditional knock out in excitatory neurons ( Kim et al, 2018 ), conditional knock out in inhibitory neurons ( Kim et al, 2018 ), conditional knock out in parvalbumin-positive neurons ( Lee et al, 2018 )], deletion of exon 24 [knock out ( Pappas et al, 2017 ), conditional knock out in Purkinje cells ( Pappas et al, 2017 ), conditional knock out in excitatory neurons of neocortex and hippocampus ( Pappas et al, 2017 )]. All these models display hyperactivity, except the mice mutated conditionally only in Purkinje cells ( Ha et al, 2016 ; Peter et al, 2016 ; Pappas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it contributed to our understanding of genetic and molecular mechanisms underlying complex behaviors, such as circadian rhythm, anxiety, and cognitive functions 16 . This progress is based on establishing a variety of assays for mouse behavioral phenotyping which has been developed over the years to maximize the scope and reproducibility of findings, minimize artifacts and false-positive results and provide robust and valid translational tools for testing hypotheses and developing novel treatments 17,18 .…”
mentioning
confidence: 99%
“…Behavioral tests in mice are mostly burdened by inherent complexity and require consideration of several aspects such as sources of variability and experimental interference that could preclude spontaneous behavior 19 . The choice of the behavioral test is another important issue, and several tests exist for different behavioral categories covering a wide range of neuropsychiatric symptoms 18 . Furthermore, recapitulating the behavioral features of a human disease is a prerequisite for the translation of preclinical results into clinical applications 20 .…”
mentioning
confidence: 99%